Music-Aesthetic Education of Primary School Pupils - Vovk, Valentyn; Yarova, Maryna (Pedagogical Discourse, 2017)
The article draws attention to the fact that in the State National Program «Education» (Ukraine of the XXI Century) it is stated that one of the ways of reforming the content of humanitarian education is to ensure the aesthetic development of the personality, the acquisition of the values of various branches of art. Besides, the state standard of primary general education determines, as one of the primary tasks, the rise of priority of primary education and upbringing, the formation of the attitude to the junior school age as a responsible stage of the child’s life. It is in the younger school age that the development, formation and growth of aesthetic feelings, cognitive abilities, artistic interests, fantasy, and mastery of practical skills are the most intense. The State standard of primary general education includes the educational branch «Art», the purpose of which is the development of personal-value attitude to art, the ability to perceive, understand and create artistic images, artistic-creative self realization and spiritual self improvement. The music-aesthetic education of primary school pupils can be defined as the formation of their aesthetic attitude to the reality, the content of which, combining common to mankind, epochal, regional, national, professional and individual traits, carries historically certain level of humanity. The ways of enriching the spiritual-creative potential of children are diverse, but the music- aesthetic education in this process is the main thing. It serves as the final, concluding element of the system of general education. Mass music education forms artistic-figurative thinking, awakens and develops natural emotional sensitivity, personal-value attitude to art, ability to perceive, active versatility, understanding and creation of artistic images, needs for artistic-creative self realization and spiritual self perfection. Music has always been and remains one of the most powerful means of moral-aesthetic education, since the power of its influence on a person has been tested during the centuries.